Incorporation of carboxyl and amino functionalized carbon quantum dots in thin film membrane for nanofiltration - Nur Hafizah Zainal Abidin; Siti Nur Alwanie Shafie; Hazwani Suhaimi; Nonni Soraya Sambudi; Nik Abdul Hadi Sapiaa Md Nordin (Polymer Testing, 2021)
Fabrication of thin film nanocomposite membrane (TFN) with carbon quantum dots (CQDs) as nanofiller has gained a wide attention due to the promising properties of the CQDs to enhance the membrane permeability. Synthesis of CQDs and their functionalization with both carboxyl and amino groups are originated from rice husks as the precursor. Fourier-Transform Infrared Spectroscopy (FTIR) analysis shows that CQDs contain oxygen-containing groups that allow hydrogen bonding with water molecules. Zeta potential shows that the incorporation of CQDs produces highly negative charged membranes, while Field Emission Scanning Electron Microscopy (FESEM) and Atomic Force Microscopy (AFM) results indicate that the introduction of the nanoparticles alters the surface properties of the fabricated membranes. Photoluminescence (PL) analysis proves that CQDs are present in the polyamide (PA) layer which describes the unique characteristic of the CQDs. The presence of CQDs in TFN membranes assists in enhancing the performance of pristine thin film composite (TFC) membrane in both flux and salt rejection with values around 35 L/m2 h and 90%, respectively.